2018
DOI: 10.1186/s13287-018-1070-3
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the role of mesenchymal stem cells in urinary bladder regeneration—a preclinical study on a porcine model

Abstract: BackgroundThe tissue engineering of urinary bladder advances rapidly reflecting clinical need for a new kind of therapeutic solution for patients requiring urinary bladder replacement. Majority of the bladder augmentation studies have been performed in small rodent or rabbit models. Insufficient number of studies examining regenerative capacity of tissue-engineered graft in urinary bladder augmentation in a large animal model does not allow for successful translation of this technology to the clinical setting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Meanwhile, MSCs may stay undifferentiated and release growth factors, which act as a feeder layer rich in trophic factors that trigger the migration of native cells from the surrounding tissues. At this point, a recent study concerning bladder tissue regeneration revealed that differentiation plays a minor role in the final regeneration effect mediated by MSCs [13]. Furthermore, BMSCs are commonly used in differentiating into SMCs and urothelium in the case of bladder tissue regeneration [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, MSCs may stay undifferentiated and release growth factors, which act as a feeder layer rich in trophic factors that trigger the migration of native cells from the surrounding tissues. At this point, a recent study concerning bladder tissue regeneration revealed that differentiation plays a minor role in the final regeneration effect mediated by MSCs [13]. Furthermore, BMSCs are commonly used in differentiating into SMCs and urothelium in the case of bladder tissue regeneration [35].…”
Section: Discussionmentioning
confidence: 99%
“…As two main autologous MSC types, adipose-derived mesenchymal stem cells (ADSCs), and bone marrow-derived mesenchymal stem cells (BMSCs) are generally applied in tissue regeneration investigations due to their abundance and easy access. And some previous studies have found that the source of MSCs (bone marrow vs adipose tissue) has no impact on the regeneration of tissue-engineered urinary bladder [13]. According to recent literatures, BMSCs have been proved to undergo directed differentiation toward endodermal derived urothelium and develop into mature bladder tissue in the appropriate signaling environment [14].…”
Section: Introductionmentioning
confidence: 99%
“…The self-regenerating capability is not however enough to rebuild the primary bladder wall structure. Therefore, boosting endogenous regenerative potency is necessary [5]. Stem cells stimulate regeneration of tissue-engineered urinary bladder but the molecular basis of this process remains unknown until now.…”
Section: Discussionmentioning
confidence: 99%
“…Principles of bladder tissue engineering have been established a decade after the landmark research by Atala et al, which drew the urology community’s attention on opportunities offered by regenerative medicine [3]. Stem cells, especially mesenchymal stem cells (MSCs), are the most commonly used cell population in tissue engineering, which can deliver paracrine factors that rearrange the local healing response [4, 5]. Numerous studies indicated that stem cells promote regeneration of tissue-engineered urinary bladder preventing fibrosis and scar formation [412].…”
Section: Introductionmentioning
confidence: 99%
“…Both cell-derived and tissue/organ-derived ECMs have been used is several studies and have shown the capability to direct cellular behavior ( Table 2). Cartilage Extracellular matrix Chondrogenic differentiation [133,134] Bladder Extracellular matrix Promotion of cellular proliferation and stemness [135,136] A fibroblast-derived extracellular matrix (fd-ECM) was able to induce chondrogenic differentiation of adipose-derived mesenchymal stromal cells (ad-MSCs) in vitro [91]. Although the Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 21 August 2019 doi:10.20944/preprints201908.0222.v1…”
Section: Cell-derived Ecms Versus Tissue/organ-derived Ecmsmentioning
confidence: 99%